ZnO/ZnFe2O4/N-doped C micro-polyhedrons with hierarchical hollow structure as high-performance anodes for lithium-ion batteries. (December 2017) - Ma, Yuan; Ma, Yanjiao; Geiger, Dorin; Kaiser, Ute; Zhang, Huang; Kim, Guk-Tae; Diemant, Thomas; Behm, R. Jürgen; Varzi, Alberto; Passerini, Stefano
Abstract: In this work, a facile and potentially scalable self-template synthesis of bi-component ZnO/ZnFe2 O4 /N-doped C micro-polyhedrons with hierarchical hollow structure (ZZFO-C) is presented. These are obtained through calcination of a single bi-metallic metal-organic framework (MOF) precursor (ZIF-ZnFe, molar ratio of 3:1). The resulting material shows a high surface area and is constituted by the organized assembly of numerous nanoparticles sub-unit (with size in the range of 20 nm). By tuning the annealing conditions, porous ZnO/ZnFe2 O4 (ZZFO) micro-polyhedrons are obtained. The ZZFO-C composite materials are studied as anodes for LIBs exhibiting remarkable energy storage performance, such as, large reversible capacity (ca. 1000 mA h g −1 after 100 cycles at 200 mA g −1 ), excellent rate capability and cycling stability. After high-rate capacity testing (1000 cycles at 2.0 A g −1 ), ZZFO-C shows an excellent reversible capacity of 620 mA h g −1 . The excellent performance of ZZFO-C arises from its unique hierarchical hollow structure and the synergy between the two active components and the N-doped carbon matrix. The electrochemical reaction mechanism and structure phase changes upon the initial lithiation are identified via in situ X-ray diffraction studies. Graphical abstract: Highlights: ZnO/ZnFe2 O4 /N-doped C micro-polyhedrons with hierarchical hollow structure (ZZFO-C). ZZFO-C material exhibits remarkable energy storage performance as LIB anode. ZZFO-C shows synergy between the two active components and the N-doped carbon matrix. The reaction mechanism of ZZFO-C is revealed via in situ X-ray diffraction studies.